Data from 14, 597 penile measurements of vietnamese men. (9th February 2021) - Nguyen Hoai, Bac; Pham Minh, Quan; Nguyen Cao, Thang; Sansone, Andrea; Colonnello, Elena; Jannini, Emmanuele A.
Abstract: Background: Penis size is a highly sensitive topic, which has often raised concerns associated with human masculinity and male sexual health. Although data regarding penile dimensions have been published worldwide, little is known about these measurements in South‐East Asian countries. Objective: This study aimed to provide the reference range in penile length, circumference, and diameter of Vietnamese men and their variations among men with erectile dysfunction and other diseases. Materials and Methods: Information about flaccid length, stretched length, mid‐shaft circumference, and glans diameter from the health records of 14, 597 men attending the Andrology Consultation was collected. These men were classified into three groups being regular reproductive health screening group, sexual dysfunction group, and other disease groups. Results: We found that penile dimensions follow a non‐parametric distribution, as tested by Kolmogorov‐Smirnov test. The median values are 9.03 cm for flaccid length, 14.67 cm for stretched length, 8.39 cm for mid‐shaft circumference, and 2.86 cm for unaroused glans diameter. Length and girth of the penis also changed among the different groups, especially in flaccid state; specifically, men with erectile dysfunction had a greater value in all penile dimensions except for change ratio compared with other groups. Circumcision, which rarely occurs in Vietnam, was associated with a 2 mm reduced penis length. Discussion: Findings on correlations between penile dimensions and somatometric parameters from previous studies are questionable and some measurements, such as glans dimension, have not been thoroughly investigated so far. Nevertheless, penile dimensions provide useful insight concerning conditions affecting sexual development and might be a valuable parameter in the assessment of erectile dysfunction. Conclusion: Results of this study provide informative materials for the assessment of penile size, including reference values drawn from a large sample of Vietnamese men that can be useful in clinical practice and sexual health education.